2021
DOI: 10.1186/s12245-021-00391-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department point-of-care ultrasound for upper extremity deep venous thrombosis ED POCUS for upper extremity DVT

Abstract: Background Upper extremity deep vein thrombosis (UEDVT) is an uncommon disease but has to be carefully considered in patients with isolated unilateral upper limb swelling due to its potential to cause devastating complications and sequelae such as pulmonary embolism and septic thrombophlebitis. Given the extreme rarity of this condition, it is not surprising that point-of-care ultrasonographic evaluation of the upper limb for deep venous thrombosis is hardly ever performed in the emergency depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A high frequency linear array transducer should be used with the vascular preset. As some of the upper limb deep veins are difficult to compress, the examination may need to rely on finding the echogenic clot and lack of spontaneous or augmented flow using colour Doppler [ 11 ]. The transducer should be placed in a transverse position over the sternocleidomastoid muscle to evaluate the IJ vein.…”
Section: Discussionmentioning
confidence: 99%
“…A high frequency linear array transducer should be used with the vascular preset. As some of the upper limb deep veins are difficult to compress, the examination may need to rely on finding the echogenic clot and lack of spontaneous or augmented flow using colour Doppler [ 11 ]. The transducer should be placed in a transverse position over the sternocleidomastoid muscle to evaluate the IJ vein.…”
Section: Discussionmentioning
confidence: 99%
“…Limited case reports have shown ability to detect upper extremity and IJV thrombi with POCUS. 3,4,[33][34][35][36] Only a single report of 3 patients involved the use of POCUS in the PED. 33 To our knowledge, this is the first report of IJV septic thrombophlebitis diagnosed by POCUS in the PED.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…There is a paucity of data in the pediatric population, although Watkins et al 32 showed 100% agreement between radiology and POCUS evaluation of lower extremity DVT in a small pediatric population. Limited case reports have shown ability to detect upper extremity and IJV thrombi with POCUS 3,4,33–36 . Only a single report of 3 patients involved the use of POCUS in the PED 33 .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…POCUS techniques come with a false-negative rate of 4% when compared with radiology-performed exams, and POCUS algorithms may miss distal DVTs that have been implicated in a higher proportion of PE 15. The use of POCUS to identify upper extremity DVT is less well described, limited to case reports without evidence of sensitivity or specificity 24. This limitation is particularly concerning when examining inpatients and the critically ill as upper extremity DVT is much more likely in the setting of upper extremity intravenous catheters, cancer, and severe illness 18…”
Section: Ultrasound For Deep Vein Thrombosis (Dvt) Assessmentmentioning
confidence: 99%
“…15 The use of POCUS to identify upper extremity DVT is less well described, limited to case reports without evidence of sensitivity or specificity. 24 This limitation is particularly concerning when examining inpatients and the critically ill as upper extremity DVT is much more likely in the setting of upper extremity intravenous catheters, cancer, and severe illness. 18…”
Section: Limitationsmentioning
confidence: 99%